Istihsan as a Finding Method of Progressive Islamic Law in the Industrial Revolution Era 4.0 - Diky Faqih Maulana; Abdul Rozak (INSTITUT AGAMA ISLAM NEGERI PALANGKA RAYA, 2021)
ABSTRACTThe rapid development of generations and science raises various new problems that are not only solved by the legal sources of the Qur'an and Hadith. Istihsan is a way of finding Islamic law, which is used as a proposition (dalil) in Hanafi fiqh. The article examined the role of istihsan as a finding method of progressive Islamic law. The research was descriptive-analytical with a normative approach. Istihsan is another most decisive option in finding Islamic law, because many contemporary things in the era of the industrial revolution 4.0, such as eye transplant law, buying and selling without qabul lafdzi at mini markets, and transactions on vending machines and online shops have been completed using the istihsan method, as well as establishing the laws. The essential goal of istihan is to eliminate madorot (harm) and achieve maslahah (benefits). While maslahah is the goal of value in the establishment of progressive Islamic law. istihsan is very possible to be developed and modified as a method of establishing the law that is dynamically and develops following the times.Keywords: Istihsan, Progressive Islamic Law, Industrial Revolution Era 4.0.ABSTRAKPesatnya perkembangan generasi dan ilmu pengetahuan, menimbulkan berbagai problem baru yang tidak hanya diselesaikan dengan sumber hukum al-Qur’an dan Hadis. Istihsan adalah cara menemukan hukum Islam yang dijadikan dalil dalam fiqih Hanafi. Tulisan ini akan mwngkaji peran istihsan sebagai metode menemukan hukum Islam yang progresif. Penelitian ini bersifat deskriptif analitis dengan pendekatan normatif. Istihsan menjadi opsi lain yang paling menentukan dalam menemukan hukum Islam, karena banyak hal kontemporer di era revolusi industri 4.0 seperti hukum pencangkokan mata, transaksi jual beli tanpa ijab qabul lafdzi pada mini market, transaksi pada vending machine dan transaksi online shop telah diselesaikan dengan metode istihsan dan hukum yang ditetapkan. Tujuan esensial dari istihsan adalah menghilangkan madorot dan mencapai maslahah. Sedangkan kemaslahatan adalah nilai yang ingin dicapai dalam pembentukan hukum Islam yang progresif. istihsan sangat memungkinkan untuk dilakukan pengembangan dan modifikasi sebagai metode penetapan hukum yang bergerak dinamis dan berkembang yang sinkron dengan perkembangan zaman.Kata Kunci: Istihsan, Hukum Islam Progresif, Era Revolusi Industri 4.0.